UMBILICAL RECONSTRUCTION WITH DOUBLE OPPOSING SEMILUNAR FLAP, AN APPEALING RESULTS: A CASE SERIES - Muharram, Arif Rahmat; Budi, Agus Santoso; Zarasade, Lobredia; Beta Subakti Nata’atmadja (Jurnal Rekonstruksi dan Estetik, 2018)
Highlights: A double opposing semilunar flap has good result for umbilicus reconstruction. A double opposing semilunar ensures a natural appearance and avoids visible scarring while maintaining appropriate depth and size. Abstract: Introduction: Umbilical loss is not a common problem encountered in plastic surgery routine cases. The absence of umbilicus will cause significant effect in total aesthetic appearance of the abdomen, thus making it an essential part of anatomy landmark. Congenital defect, oncologic and abdominoplasty complication are the most often causes, and tremendous psychological trauma will cause patient to seek help. Case Illustration: There are many proposed technique for such reconstruction, based on original scar or wound and final expected shape, of course with their advantages and disadvantages. We used a double opposing semilunar flap for our cases. Along with its technical detail, we will present three cases comprises of the defect after omphalocele scar removal, umbilical endometriosis excision and postcentral abdominal tumor excision. Reports will be presented with preoperative and postoperative result. Discussion: This technique avoids the appearance of scarring and secondary stenosis by hiding the circular scar incision and maintaining its position in the middle of the new form. Conclusion: The reconstruction technique of the umbilicus presented for the anatomical units, provides a very natural look, and generates slight excess of skin on the upper part over time and giving a more graceful appearance.